La calidad de servicio y su relación con la satisfacción del cliente en el restaurante Punta Salinas - Iquitos 2023 - Padilla Patow, Maria de Fatima (2024)
The objective of this research was to determine how the quality of service is related to customer satisfaction at the Punta Salinas Restaurant - Iquitos 2023, the methodology used was correlational, descriptive, non-experimental design. The sample was made up of 115 clients who attended the Punta Salinas Restaurant. The results obtained indicate that the service quality variable in its dimensions, tangible elements, were beneficial for 58.2% of clients; empathy is good for 53%; reliability is good for 55.7%; 57.4% of clients had good response capacity, and for 53.1% of clients, security is good. Regarding the variable customer satisfaction in its functional performance dimensions, 56.5% of customers are pleased; With the level of satisfaction, 53% are pleased and with respect to the fulfillment of their expectation, 57.4% are pleased. Conclusion In the research, it was determined that the variables quality of service and customer satisfaction in the Punta Salinas restaurant in 2023 are significantly related (p=0.000)